THE INFLUENCE OF MOTIVATION, ENTREPRENEURIAL KNOWLEDGE AND FAMILY ENVIRONMENT ON INTEREST IN ENTREPRENEURSHIP IN MANAGEMENT PROGRAM STUDENTS OF MUHAMMADIYAH PONOROGO UNIVERSITY - Dina Ismaya; Sri Hartono; Fery Setiawan (Yayasan Nuraini Ibrahim Mandiri, 2024)
Most people today still depend on being office employees rather than being entrepreneurs. This is what underlies the large number of unemployed, because existing companies cannot accommodate all prospective workers. The country of Indonesia still really needs new entrepreneurs because it is hoped that the increasing number of entrepreneurs in Indonesia can open up new job opportunities so that it can reduce the unemployment rateThis research aims to analyze the influence of Motivation, Entrepreneurship Knowledge and Family Environment on Entrepreneurial Interest in Management Study Program Students, Faculty of Economics, Muhammadiyah University, Ponorogo. The sample was Management Students from the 2019 and 2020 class of Muhammadiyah University of Ponorogo using a sampling technique, namely Accidental Sampling and a sample of 100 respondents. The analysis used in this research uses multiple linear regression analysis using tools, namely the SPSS 25 program. This research produces a partial test (t) which is as follows: Motivation (X1) = 0.000, Entrepreneurship Knowledge (X2) = 0.001, and Family Environment ( X3) = 0.003